Factors that influence job satisfaction in oil palm plantation / Muhamad Fais Ismail - Ismail, Muhamad Fais (Faculty of Plantation and Agrotechnology, 2019)
Job satisfaction is a feeling of a person either satisfies or dissatisfy toward their employment. Company that provides employment needs to ensure that their company provides positive job satisfaction among worker to obtain best performance from their workers. This study investigates three independence factors (pay, communication and working condition) toward job satisfaction with sample of 52 workers that work in the Lembah Kesang oil palm plantation. The objectives for this study are to investigate the relationship between all independent factors toward the jobs satisfaction of workers and to determine the most influence factor that contributes with job satisfaction. The method for this research is by doing survey that using questionnaires. The data that have been collected are analyzed using correlation coefficient and regression from the software Statistical Package for Science (SPSS). The results from correlation coefficient analysis show all independence (pay, communication and working condition) factors have significant relationship with the job satisfaction. The result from regression analysis show that the working condition is the most influence factors that contribute to the job satisfaction with value of (beta=0.249). As for the recommendation, the management at the Lembah Kesang plantation need to make a long term plan to improve the working condition as the factor has high contribution to their company. The management of the oil palm estate can use the finding to improve the factor of communication, pay and working condition in their estate to increase the job satisfaction among workers as all factors show a significant relationship with job satisfaction among workers in oil palm plantation.